Enhanced dielectricity coupled to spin-crossover in a one-dimensional polymer iron(ii) incorporating tetrathiafulvalene. Issue 24 (8th June 2020) - Qiu, Ya-Ru; Cui, Long; Cai, Pei-Yu; Yu, Fei; Kurmoo, Mohamedally; Leong, Chanel F.; D'Alessandro, Deanna M.; Zuo, Jing-Lin
Abstract : A concerted bending–flattening motion of the redox-active TTF within constructed one-dimensional Fe II –TTF–Schiff-base chain with bridging 4, 4′-bpy enhances the dielectric constant coupled to its spin-crossover transition above room temperature. Abstract : In designing multifunctional materials for potential switches that can be used as memory devices, the high-spin (HS) to low-spin (LS) crossover (SCO) one-dimensional polymer, [Fe II (L)(4, 4′-bpy)] n, was constructed from a designed redox-active tetrathiafulvalene (TTF) functionalized Schiff-base and the ditopic linker 4, 4′-bipyridine (bpy). It exhibits an 8 K hysteretic SCO centred at T 1/2 = 325 K which is coupled to changes in its dielectric constant. The crystal structures above and below the transition temperature reveal similar parallel linear ⋯Fe–bpy–Fe–bpy⋯ chains displaying expansion of the Fe II octahedron in the HS state. Density functional theory (DFT) calculations reveal a concerted electronic charge and spin change represented by the Mülliken charge of the Fe and the magnitude and direction of the dipole moment which substantiate the experimental observations.